Projection of glacier changes over the Laohugou Glacier No. 12, Northeast Tibetan Plateau, China from 2020 to 2100 - Mengyuan Liu; Baojuan Huai; Lei Wang; Yuzhe Wang; Hongmin An; Jizu Chen; Wentao Du; Xiang Qin; Weijun Sun (Journal of Hydrology: Regional Studies)
Study region: Laohugou Glacier No. 12 in the Qilian Mountains, northeast Tibetan Plateau. Study focus: Alpine glacier meltwater from the Qilian Mountains (QMs), northeast Tibetan Plateau, is the main source of water for the surrounding arid zones. Accurately reconstructing long-term mountain glacier mass balance (MB) and projecting glacier changes under climate warming are pivotal in cryospheric scientific research. In this study, Laohugou Glacier No. 12 (LHG12), in the western QMs, was selected as a study area. Based on the Coupled Model Intercomparison Project (CMIP6) models, the degree-day and glacier retreat models were used to predict the glacier changes under three scenarios for 2020–2100. New hydrological insights for the region: From 2020–2100, the annual mass loss of LHG12 simulated using CanESM5 and EC-Earth3 which perform best increased compared to the measured data in the historical period (2010–2014) (i.e., annual MB of −0.26 m w.e) by a factor of 1.04 and 1.73 under SSP1–2.6, 4.62 and 4.88 under SSP3–7.0, and 6.23 and 7.15 times under SSP5–8.5. By 2100, the ice volume and area of LHG12 simulated using CanESM5 and EC-Earth3 reduced to 0.03×109 (1.6 %) and 0.01×109 (0.4 %) m3, 1.87 and 0.75 km2 under SSP5–8.5, respectively.